PELAKSANAAN PEMBELAJARAN DENGAN METODE DISKUSI OLEH GURU PAI DI SMA NEGERI 1 SITIUNG KABUPATEN DHARMASRAYA - Juramika, Juramika (El -Hekam, 2019)
The purpose of this study was to describe and analyze the planning, implementation and evaluation of learning by the method of discussion by PAI teachers at SMAN 1 Sitiuang. The results of the study show that, (1). Learning planning with the method of discussion by PAI teachers at SMAN 1 Sitiung Dharmasraya District is in planning learning PAI teachers must prepare learning devices so that students' learning achievement in Islamic Religious Education subjects increases, learning tools must be prepared by PAI teachers, including understanding curriculum, mastering teaching materials, compiling teaching programs, implementing teaching programs, assessing teaching programs and the results of the teaching and learning process that has been implemented. (2). The implementation of learning is in implementing learning methods to improve the learning achievement of students of Islamic religious education, PAI teachers always support and direct students to be enthusiastic in learning so that their learning achievements will increase. (3). Implementation Evaluation, namely by holding several routine activities to determine the extent to which the students have understood the material that has been thoroughly delivered by the teacher. Such activities such as the Daily Deuteronomy after the completion of one material were delivered, the PAI teacher held a Daily Examination with the aim of being used as a benchmark, the extent to which the students were able to understand and accept the material that had been delivered by PAI teachers.